QUALITATIVE AND QUANTATIVE APPROACHES TO TYPOLOGIZE PARTY SYSTEMS - Назаров, М.С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The article describes the qualitative, quantitative and mixed approaches to the typology of party systems. The attempt was made to analyze each of the approaches identifying both strengths and weaknesses of its sides. At the end of the study the author focuses on the most successful in his view typology, which should be used in further studies.